FUNGSI HUKUM DALAM KEHIDUPAN MASYARAKAT - Didiek R. Mawardi (Masalah-Masalah Hukum, 2015)
The function of law as a means to achieve social justice , the reality in the life of society , there has been a shift in values  and or cultural order , ignorance of the norm of honesty , the degrdation of the feeling of shame , nor loss of trust in the legal and law enforcement , compliance with laws decreased, causing law dysfunction . The problem that arises is why the function of the law has not been fully realized and how to optimize the function of law in society. There is no other option , that the substance of the law and arbitrate should significantly oriented and argue the morality to the formation of a prosperous society ( Indonesia ) through the process of empowerment of the legal system , through a process of dialogue , as well as raise community participation .